Cultural musicology : new perspectives on World War II - Fauser, Annegret 1963- (Zeithistorische Forschungen, 2011)
The study of organized sound is the business of musicology – yet this routine observation carries a wealth of complexities, especially in the context of interdisciplinary discourse. Although musicology’s pluridisciplinary foundations offer open access to such disciplines as history, literary studies, mathematics, or sociology, the field’s intradisciplinary discourses and methodologies have shaped musicology in ways that turn most interdisciplinary exchange into a challenge. The scholarly exploration of sound in the twentieth century presents a case in point. Meaningful research on, for example, the music of the contemporary avant-garde composer Kaija Saariaho demands highly sophisticated technical skills in the spheres of the analysis, aesthetics, and technologies of music. While one could imagine interdisciplinary research on Saariaho involving, for example, the humanities or social sciences – perhaps with respect to, say, cultural politics in the late twentieth century – the specialist areas of music research usually remain disciplinarily hermetic. My current work on music in the USA during World War II offers striking examples of the need for, yet problems of, squaring interdisciplinary engagement with intradisciplinarities. The following remarks will address some of those disciplinary intersections.